19 BCR SERINE/THREONINE KINASE ENHANCES ANGIOTENSIN II-MEDIATED NUCLEAR FACTOR κB TRANSCRIPTIONAL ACTIVATION IN VASCULAR SMOOTH MUSCLE CELLS VIA INHIBITION OF PEROXISOME PROLIFERATOR-ACTIVATED RECEPTOR γ. (1st March 2007) - Alexis, J.; Che, W.; Ding, B.; Ito, S.; Wang, N.; McClain, C.; Korshunov, V.; Berk, B. C.; Yan, C.; Abe, J.
Abstract : Bcr is a serine/threonine kinase and is highly expressed in the neointima after vascular injury. Because angiotensin II (Ang II) and inflammation play important roles in the development of intimal proliferation, we hypothesized that Bcr is an important regulator of Ang II-mediated nuclear factor (NF)-κB activation. By transfecting vascular smooth muscle cells (VSMCs) with dominant negative Bcr (DN-Bcr), we demonstrated that DN-Bcr inhibited Ang II-mediated NF-κB activation in VSMCs (82 ± 10% inhibition, n = 3, p < .01). Similarly, we demonstrated that Bcr siRNA inhibited Ang II-mediated NF-κB activation in VSMCs (79 ± 7%, n = 3, p < .01). In a survey of nuclear factors that might regulate NF-κB activation, we found that wild-type (WT) Bcr decreased ligand-mediated peroxisome proliferator-activated γ (PPARγ) activity (86 ± 12% inhibition, p < .01), whereas DN-Bcr significantly enhanced ligand-mediated PPARγ activity (2.4-fold, p < .01). Assessment by in vitro kinase assay demonstrated that Bcr phosphorylates PPARγ. Overexpression of WT-Bcr kinase did not inhibit ligand-mediated PPARγ1 S82A or S82D mutant transcriptional activity, suggesting that Bcr regulates PPARγ activity via S82 phosphorylation. To assess the physiologic role of Bcr, we examined the effect of Ang II on Bcr expression and transcriptional activation. Using VSMCs, we demonstrated that Ang II only weakly increases Bcr kinase activity but significantly increased its expression after 6 hours of Ang II stimulation (4.3 ± 0.8-fold increase, p < .01). In addition, we found that whereas Ang II inhibits PPARγ activation, Bcr siRNA reverses Ang II inhibition of PPARγ. To determine the role of Bcr/PPARγ on Ang II-mediated NF-κB activation, we cotransfected VSMCs with DN-Bcr and DN-PPARγ. We found that DN-PPARγ reversed DN-Bcr-mediated inhibition of NF-κB activation. In addition, WT-Bcr-induced NF-κB activation was inhibited by PPARγ1 S82A mutant but not WT-PPARγ1, strongly suggesting that Bcr-induced inhibition of PPARγ activity reciprocally increases NF-κB activation and regulates Ang II-mediated NF-κB activation. Finally, our preliminary data suggest a decrease in intima to media ratio (0.31 vs 0.73) in Bcr knockout mice compared with controls in a partial ligation model of the left carotid artery. Given our findings that Bcr kinase inhibits PPARγ activation and enhances Ang II-mediated NF-κB transcription, we believe that Bcr acts as an important regulator of the sensitivity of VSMCs to inflammatory stimuli.